Analisis Kesulitan Pembelajaran Daring pada Mata Pelajaran Matematika di Tengah Pandemi Covid-19 - Riskawati Riskawati; Novianita Achmad; Nursiya Bito (Jambura Journal of Mathematics Education, 2021)
This study aims to describe the difficulties of online learning in mathematics subjects in the midst of the Covid-19 pandemic. This research is a descriptive research with a quantitative approach. The subjects in this study were students of class VIII 3 and VIII 4 at SMP Negeri 4 Gorontalo. Data collection was obtained from data from questionnaires and student interviews. To see student responses in online learning on mathematics subjects in the midst of the Covid-19 pandemic, a questionnaire was given with indicators, namely: (1) Difficulty in accessing the internet network and operating online media during learning, and (2) Difficulty in understanding objects, facts, concepts, principles and mathematical operations. Based on the data obtained from 61 students, there were 8 students in the high category, 41 students in the moderate category and 12 students in the low category. This means that the difficulty level of online learning in mathematics subjects in the midst of the Covid-19 pandemic in class VIII of SMP Negeri 4 Gorontalo is in the Medium category.